Life history of thrips hawaiiensis (Morgan) reared on flower of "saba" banana (Musa acuminata x balbisiana Colla) - Reyes, Cecilia P.; Copuyoc, Maria Katherine M.; Castillo, Jamaica T.; Guzman, Junel B. (2021)
"Thrips hawaiiensis (Morgan) is a pest of banana, mango, and pomelo. The study aimed to determine the development and reproductive capacity of thrips under laboratory conditions. To start the culture, female thrips were collected from Beltran "Saba" banana plantation in Tuao, Cagayan, Philippines" - title page.
Includes bibliographical references.
Keywords: Bananas -- Philippines -- Diseases and pests; Insect rearing -- Philippines; Insects -- Development -- Philippines; Thrips -- Philippines